Lipomatous angiomyofibroblastoma: A 20-year literature review - Julie Guilmette, MD; Philippe Gauthier, MD, FRCSC; Kurosh Rahimi, MD, FRCPC (Elsevier, 2015)
Lipomatous angiomyofibroblastoma (LAMF) is a rare superficial muco-cutaneous tumor of the female genital tract in women of reproductive age and early menopause. We report the case of a 36-year-old woman who presented with an asymptomatic 1 cm round vulvar mass. The tumor showed both hypercellular and hypocellular areas composed of spindle and epithelioid cells set in a loose fibromyxoid background. Anastomosing networks of small to medium sized dilated vessels, surrounded by condensed spindle cells, were distributed equally throughout the tumor. Mature adipocytes comprised more than half of the tumor's volume. The neoplastic cells were reactive for both desmin and vimentin and did not express CD34, smooth muscle actin, S100 protein and muscle-specific actin. Making the right diagnosis may be challenging to medical professionals as LAMF may mimic both clinically and histologically several other benign and malignant gynecological lesions. LAMF has a benign course without evidence of local recurrence or metastatic potential.